Planejamento urbano em Maringá, uma primazia sob suspeita : o início dos aportes do BNH e seus desdobramentos no território - Garcia, Carla Fernanda Rocha (2015)
This research is dedicated to advancing of understanding of spatial reproduction process in Maringá-PR, under the influence of state power during the military government, more precisely during the administration of Silvio Barros I (1973-1976). This moment was marked by the first loans from the Banco Nacional de Habitação which, through its credit lines, among them the CURA Program (Comunidade Urbana de Recuperação Acelerada), represent the beginning of the process in urban acceleration in Maringa. This dynamic, even applied in a planned city, produced similar problems to those produced by metropolitan cities, characterized by population growth and abrupt territorial expansion. In Maringa, the funds coming from the BNH were consumed primarily in the structuring of the road network, implementation of urban infrastructure and construction of public housing.The large investments from the federal programs, in addition to causing major impact on physical and territorial structure of the city, carved the administrative and institutional structure. A significant milestone related to urban planning in this period was the creation of Eteplan (Escritório Técnico de Planejamento), followed by its extinction. The planning office, equipped with financial and administrative autonomy, had conducted several studies and updated the cadastral map of the city. Indicated by the Master Plan of 1967, the Eteplan constituted a technical face planning in the ordering of the city's growth. The agency was abolished in the same year that has begin the loans. This research aims to demonstrate that these great contributions, coming from Federal Government in Maringa, has induced changes in the political administrative structure of the municipality, to include and contemplate the new actors that required participants in the process of application of these appeals.